Chronic Airway Diseases Early Stratification (CADSET): a new ERS Clinical Research Collaboration. Issue 3 (19th March 2019) - Agusti, Alvar; Faner, Rosa; Donaldson, Gavin; Heuvelin, Elise; Breyer-Kohansal, Robab; Melén, Erik; Maitland-van der Zee, Anke H.; Vestbo, Jørgen; Allinson, James P.; Vanfleteren, Lowie E.G.W.; van den Berge, Maarten; Adcock, Ian M.; et al.
A recent editorial in the European Respiratory Journal highlighted the strategic importance of the Clinical Research Collaborations (CRCs) launched in 2013 by the European Respiratory Society (ERS) [1]. These have the aim of 1) promoting the exchange of research ideas among clinicians and affiliated scientists in Europe and/or globally; 2) building an infrastructure for prospective clinical research; 3) securing additional funding through national and European Union funding streams; and 4) facilitating the planning, implementation, evaluation and publication of clinical and translational studies at pan-European level and beyond. So far, there are currently 17 ongoing CRCs that cover eight major respiratory disease domains (airway diseases, interstitial lung diseases, pulmonary vascular diseases, sleep and breathing disorders, respiratory critical care, paediatric respiratory diseases, respiratory infections and thoracic oncology), all of them linked to one or more ERS assemblies [2–12]. The ERS launches a new Clinical Research Collaboration (CADSET) to study the determinants and implications of different lung function trajectories through life http://ow.ly/nf4E30nGsJG